Species Composition, Distribution, Life Forms and Folk Nomenclature of Forest and Common Land Plants of Western Chitwan, Nepal - Dangol, DR (Journal of the Institute of Agriculture and Animal Science, 2005)
This paper enumerates 349 plant species belonging to 77 families of vascular plants collected in the winter seasons of 1996 and 2000 by the flora teams of the Population and Ecology Research Laboratory, Nepal. Of the total species, 249 species belong to dicotyledons, 87 species to monocotyledons and 13 species to pteridophytes. Among the families, dicotyledons contributed the highest number of families (55 in number) followed by monocotyledons and pteridophytes. In the study areas, species composition varies with the type of habitats in the study plots. Some species are unique in distribution. The highest unique species are contributed by common lands (87 spp.), followed by the Chitwan National Park forest (36 spp.) and Tikauli forest (32 spp.). Ageratum houstonianum Mill., Cynodon dactylon (L.) Pers., Imperata cylindrica (L.) Beauv., Rungia parviflora (Retz.) Nees, Saccharum spontaneum L. and Thelypteris auriculata (J. Sm.) K. Iwats are the most common species across all the research blocks. Of the listed plants, many plants have local names either in Nepalese or other tribal languages. Plants are named in different ways on the basis of habit, habitat, smell, taste, and morphological characters of the plants, which are also the basis of nomenclature in plant taxonomy. Key words: Folk name, plant biodiversity, plant distribution, species composition analysis J. Inst. Agric. Anim. Sci. 26:93-105 (2005)